Pengaruh Prenatal Yoga Terhadap Tekanan Darah Pada Ibu Hamil Dan Denyut Janin di RST Dr Asmir Salatiga - Meylinda Anadella Dewi; Rinda Intan Sari; Vivi Sovianti (Jurnal Ventilator, 2024)
Pregnancy is a physiological process and can be pathologically risky if there are changes in blood pressure and DJJ. Therefore, to maintain stable blood pressure or DJJ, prenatal yoga is needed. The purpose of this study was to determine the effect of prenatal yoga on blood pressure and DJJ. This research method is a quasi-experimental design using a one group pretest posttest design. Sampling of 50 respondents, using an observation sheet. The results of the study showed that the majority were aged 20-35 years as many as 43 respondents (86.0%), the majority of multigravida parity as many as 42 respondents (84.0%). Analysis of the average blood pressure pre-test 91.430 and post-test 84.810. In DJJ, the average pre-test was 144.48 and post-test 135.54, before being given prenatal yoga intervention showed MAP in the pre-hypertension category and DJJ in the normal category, then after being given intervention showed MAP and DJJ in the normal category. The conclusion of the statistical test using the paired sample t test obtained a MAP P-Value of 0.000 or P-Value ? 0.05 and for DJJ P-Value 0.000 or P-Value ? 0.05, namely Ha is accepted and Ho is rejected, which means that there is an effect of prenatal yoga on Blood Pressure and DJJ. Suggestions for further researchers to be able to add variables by involving her husband.